Caballero noble desbaratado : Autobiografía e invención en el siglo XVI - Gastañaga-Ponce de León, Jose-Luis, 1967- (Book collections on Project MUSE., 2011)
First-person narrative does not always fall under the genre of autobiography. In the centuries before the genre was defined, authors often patterned their personal narratives after prestigious discourses, such as hagiography, historiography, and the literary miscellany. Caballero noble desbaratado: Autobiografía e invención en el siglo XVI [Noble Knight Disrupted: Autobiography and Invention in the Sixteenth Century] analyzes several first-person narratives from Spain and the conditions of their writing and reception. It focuses on the sixteenth-century Libro de la vida y costumbres [Book of life and customs] by Alonso Enríquez de Guzmán (14991547), the knight of the title. The study also examines the influence of other writers and the vitality of lyric poetry on both sides of the Atlantic. Although the Biblioteca de Autores Españoles has devoted a volume to Enríquez de Guzmán, there has never been a book-length study dedicated to this author. This book fills that gap and constitutes a valuable contribution to the study of autobiography in Spanish.